The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjopen-2021-051885
|View full text |Cite
|
Sign up to set email alerts
|

Nature versus urban hiking for Veterans with post-traumatic stress disorder: a pilot randomised trial conducted in the Pacific Northwest USA

Abstract: ObjectivesTo evaluate feasibility and acceptability of a group-based nature recreation intervention (nature hiking) and control condition (urban hiking) for military Veterans with post-traumatic stress disorder (PTSD).Design and settingA pilot randomised controlled trial conducted in the US Pacific Northwest.ParticipantsVeterans with PTSD due to any cause.InterventionsTwenty-six participants were randomised to a 12-week intervention involving either six nature hikes (n=13) or six urban hikes (n=13).Primary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Research across several domains has recognized the positive effect of nature connectedness on the recovery of physiological and psychological distress generated by outbreaks and social or economic crises. For instance, Littman et al [ 47 ] explored how nature contact improves psychological and physical health for military veterans with post-traumatic stress disorder. Sachdeva et al [ 48 ] stated that nature has restorative elements after times of collective stress, such as the negative psychological and social consequences of the Great Recession in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research across several domains has recognized the positive effect of nature connectedness on the recovery of physiological and psychological distress generated by outbreaks and social or economic crises. For instance, Littman et al [ 47 ] explored how nature contact improves psychological and physical health for military veterans with post-traumatic stress disorder. Sachdeva et al [ 48 ] stated that nature has restorative elements after times of collective stress, such as the negative psychological and social consequences of the Great Recession in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in various populations has shown that outdoor exercise interventions are associated with improved mental health outcomes, such as reductions in tension, anger, hostility, hopelessness, and suicidal ideation ( Morita et al, 2007 ; Lundberg et al, 2011 ; Thompson Coon et al, 2011 ; Sturm et al, 2012 ; Frumkin et al, 2017 ). Within military populations, outdoor exercise interventions demonstrated benefits for psychological health, including increased positive affect and decreased negative affect, anxiety, and PTSD symptoms (e.g., Gelkopf et al, 2013 ; Rogers et al, 2014 ; Crawford, 2017 ; Townsend et al, 2018 ; Greer and Vin-Raviv, 2019 ; Walter et al, 2019 ; Bettmann et al, 2021 ; Littman et al, 2021 ; Walter et al, 2021 ). Although research on outdoor exercise interventions for overall psychological health is growing, less is known about the effects of outdoor exercise on physical and social functioning, which are essential for operational readiness and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 3 As medicine has evolved, so have NBI. For example, treating tuberculosis with fresh air in the countryside has transformed into treating an array of maladies, including, but not limited to, high blood pressure, 4 psychosomatic disorders 5 and post-traumatic stress disorder 6 in a variety of settings ranging from city parks 7 to wildland areas. 4 8 With the emergence of NBI in the modern era, researchers are currently working to build empirical support and guidance for these interventions, including the NBI locations, outcomes and dose–response relationship.…”
Section: Introductionmentioning
confidence: 99%